The scope of the principle of judicial diligence - Felices Mendoza, María Esther (2020)
This article aims to provide the scope of the principle of judicial diligence from the perspective developed, mainly, by the IberoAmerican Code of Judicial Ethics and the Bangalore Code, two instruments that constitute the guide and support of the deontological standards of the judicial function. As well as its recognition and application in the Judicial Career Law, and the consequences for the conduct of judicial trials.